STUDYING THE DIAGNOSIS OF PERIPHERAL BLOOD AND BONE MARROW IN ANEMIA OF CHRONIC DISEASES. - Madrakhimova Nigora Shokir qizi; Fazilova Sharifa Mirhamidovna (World Scientific Research Journal, 2025)
Summary: Thus, the detection of anemia in patients determines the need for mandatory clarification of the causes of this pathological condition. Timely verification of the etiology of anemia makes it possible to start adequate therapy without delay, which determines its effectiveness and improves the quality of life of people.